An in‐depth analysis of the immunomodulatory mechanisms of intervertebral disc degeneration. Issue 4 (8th December 2022) - Song, Chao; Cai, Weiye; Liu, Fei; Cheng, Kang; Guo, Daru; Liu, Zongchao
Abstract: Intervertebral disc degeneration (IVDD) is the pathological basis of disc herniation, spinal stenosis, and other related diseases, and the lower back pain it produces lays a heavy financial burden on individuals and society. Thus, it is essential to comprehend IVDD's pathophysiology. Numerous factors, such as inflammatory factors, oxidative stress, apoptosis, matrix metalloproteinases, are linked to IVDD pathogenesis. Despite the fact that many researches has provided explanations for the pathophysiology of IVDD, these studies are typically singular, restricted, and isolated, expound only on one or two components, and do not systematically analyze and summarize the numerous influencing elements. In addition, we discovered that the incidence of many chronic diseases in the field of orthopedics may be thoroughly and systematically defined in terms of immunological systems. In order to provide a theoretical foundation for an in‐depth understanding of the pathological process of IVDD and the formulation of more effective prevention and treatment measures, this review provides a comprehensive and systematic account of the pathogenesis of IVDD from the physical to the molecular barriers of the intervertebral disc, from the nucleus pulposus tissue to the cellular to the immune‐molecular level.